2007
DOI: 10.1590/s0074-02762007005000069
|View full text |Cite
|
Sign up to set email alerts
|

T-cell responses associated with resistance to Leishmania infection in individuals from endemic areas for Leishmania (Viannia) braziliensis

Abstract: Subclinical or asymptomatic infection is documented in individuals living in endemic areas for leishmaniasis suggesting that the development of an appropriate immune response can control parasite replication and maintain tissue integrity. A low morbidity indicates that intrinsic factors could favor resistance to Leishmania infection. Herein, leishmanial T-cell responses induced in subjects with low susceptibility to leishmaniasis as asymptomatic subjects were compared to those observed in cured cutaneous leish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 31 publications
6
42
3
4
Order By: Relevance
“…It has been demonstrated that the production of this cytokine by CD4 + CD25 T cells (Tregs) is associated with persistence of the parasite and reactivation of the disease [4749]. IL-10 secretion by T H 1 cells likely is a mechanism that minimizes self-regulatory immunopathology of ACL [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the production of this cytokine by CD4 + CD25 T cells (Tregs) is associated with persistence of the parasite and reactivation of the disease [4749]. IL-10 secretion by T H 1 cells likely is a mechanism that minimizes self-regulatory immunopathology of ACL [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al [23] found the agent of visceral leishmaniasis in healthy individuals who were residents of endemic areas of L. (L.) chagasi. The existence of a subclinical infection suggests the development of an appropriate immune response that can control the replication of the parasites and maintain tissue integrity (asymptomatic individuals produced more IL-10 than cured patients), hence the possibility of serologic study [24]. Although CL is endemic in several regions of Brazil, subclinical infections have been little studied, because the infection is difficult to investigate in individuals who do not exhibit clinical signs.…”
Section: Resultsmentioning
confidence: 99%
“…A hyperimmune (mixed Th1-Th2) response is associated with a more severe disease outcome in Leishmania (Viannia) infections (13,(37)(38)(39)(40)(63)(64)(65). Recently, it has been found in human L. (V.) panamensis infection that increased Treg capacity correlates with healing (18).…”
Section: Discussionmentioning
confidence: 99%
“…CpG activation of TLR9 has led to healing in experimental autoimmune diabetes (34) and amelioration of asthma and inflammatory arthritis through downregulation of Th2 cytokines (35,36). We therefore hypothesized, in light of recent results concerning the potential role of Tregs in leishmaniasis caused by L. (V.) panamensis infection and the role of inflammation in the pathology caused by L. (Viannia) parasites (37)(38)(39)(40), that CpG under the appropriate conditions could ameliorate pathology/disease.…”
mentioning
confidence: 99%